PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA PERAWAT RUMAH SAKIT PURI HUSADA DI TEMBILAHAN) - Napitupulu, Daniel; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to analyze the effect of transformational leadership and organizational commitment toward organizational citizenship behavior (studies on nurses of RSUD Puri Husada Tembilahan). Transformational leadership as the first variable (X1), Organizational commitment as the second variable (X2), and organizational citizenship behavior as the third variable (Y). The method in this research is descriptive and quantitative by using program of SPSS 21, where the sample used by 72 nurses, sampling using the formua slovin conduted by purposive sampling and technique of data collecting through questioner. The result of this analysis using test of validity, reliability test, determination, simple linear regression test, T test and F test so it can be concluded that transformational leadership have significant effect toward organizational citizenship behavior, organizational commitment have significant effect toward organizational citizenship behavior. Transformational leadership and organizational commitment have significant toward organizational citizenship behaviorin RSUD Puri Husda Tembilahan. Keywords: transformational leadership, organizational commitment, and organizational citizenship behavior.